Pengembangan pariwisata yang berkeleanjutan melalui ekowisata - Qatrunnada, Salsabila Irbah (Maliki Interdisciplinary Journal, 2025)
Ecotourism is a form of tourism that aims to protect the environment and improve the welfare of local communities through ecotourism. In sustainable tourism, ecotourism plays an important role in reducing negative impacts on the environment while encouraging conservation and economic empowerment. This article examines the basic concepts of ecotourism and its contribution to sustainable tourism development. By protecting the environment, empowering local communities and providing environmental education for tourists, ecotourism can help preserve ecosystems and support economic growth. Ecotourism development strategies include choosing the right location, environmental management and cooperation between government, private sector and community. With proper implementation, ecotourism becomes a sustainable tourism solution by utilizing the long-term environmental, social and economic benefits.